The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/em.20496
|View full text |Cite
|
Sign up to set email alerts
|

Arsenate and dimethylarsinic acid in drinking water did not affect DNA damage repair in urinary bladder transitional cells or micronuclei in bone marrow

Abstract: Arsenic is a human skin, lung, and urinary bladder carcinogen, and may act as a cocarcinogen in the skin and urinary bladder. Possible modes of action of arsenic carcinogenesis/cocarcinogenesis include oxidative stress induction and inhibition of DNA damage repair. We investigated the effects of arsenic in drinking water on DNA damage repair in urinary bladder transitional cells and on micronucleus formation in bone marrow. F344 rats were given 100 ppm arsenate [As(V)] or dimethylarsinic acid [DMA(V)] in drink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In addition, MMA(III) and DMA(III) increased the frequency of mutations at the thymidine kinase (TK) locus in LY5178 mouse lymphoma cells but only at highly cytotoxic levels. The positive results in the TK mutation assay can be ascribed either to the fact that this assay detects a wide range of genetic alterations, including chromosomal mutations (Wang et al., 2009 ), and/or to excessive levels of cytotoxicity (OECD, 2015 ). In line with these findings, MMA(III) induced significant increases in mutagenesis at the gpt locus of Chinese hamster G12 cells only at highly cytotoxic concentrations and most mutants exhibited transgene deletions.…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, MMA(III) and DMA(III) increased the frequency of mutations at the thymidine kinase (TK) locus in LY5178 mouse lymphoma cells but only at highly cytotoxic levels. The positive results in the TK mutation assay can be ascribed either to the fact that this assay detects a wide range of genetic alterations, including chromosomal mutations (Wang et al., 2009 ), and/or to excessive levels of cytotoxicity (OECD, 2015 ). In line with these findings, MMA(III) induced significant increases in mutagenesis at the gpt locus of Chinese hamster G12 cells only at highly cytotoxic concentrations and most mutants exhibited transgene deletions.…”
Section: Assessmentmentioning
confidence: 99%
“…Since 2009, only one additional study was identified related to in vivo clastogenicity of methylated arsenicals. Wang et al (2009) conducted a study to explore whether a 1-week oral exposure of F344 female rats to 100 mg/L of DMA(V) or As(V) in drinking water, followed by a 24-h recovery period, could increase the MN frequency in the bone marrow cells. Neither DMA(V) nor As(V) exposure increased MN frequencies in the bone marrow, and DMA(V) did not increase cyclophosphamide (CP)-induced MN.…”
Section: T a B L Ementioning
confidence: 99%
“…Several methods have been reported for use in evaluating potential toxicity of drinking water, such as the Ames test, micronucleus test, and comet assay (Sujbert et al 2006;Wang et al 2009;Zegura et al 2009). The comet assay can be used to investigate chemically or physically induced single-strand breaks in DNA and has been used to evaluate mutagenic activity of surface and drinking water, and the micronucleus test can be used to detect chromosomal damage (Kummrowa et al 2003).…”
Section: Introductionmentioning
confidence: 99%